Activities of eight new beta-lactam antibiotics and seven antibiotic combinations against Neisseria meningitidis. - Scribner, R K (1982)
Each of eight new beta-lactam antibiotics was highly active in vitro against Neisseria meningitidis, and activity was not reduced by combining some of these drugs with penicillin, ampicillin, or tobramycin. Antibacterial activity and lack of antagonism between moxalactam and ampicillin was confirmed in a model of lethal meningococcal infection in mice.